Comparison of high-intensity laser therapy and combination of ultrasound treatment and transcutaneous nerve stimulation in patients with cervical spondylosis: a randomized controlled trial - Venosa, M.; Romanini, E.; Padua, R.; Cerciello, S. (Lasers in medical science, 2019)
The aim of the study was to compare the effect of high-intensity laser therapy (HILT) and a combination of ultrasound (US) treatment and transcutaneous nerve stimulation (TENS) on pain, range of motion (ROM), and functional activity in patients with cervical spondylosis (CS). A total of 84 patients with a mean age of 51.54 years (52 women and 32 men) affected by CS were enrolled in this study. Patients were randomly divided into two groups. In group A (42 subjects), patients received 12 sessions of HILT plus exercise, while in group B (42 subjects), they received a combination of US, TENS, and exercise. The outcomes measured were cervical segment ROM, pain level measured by visual analogue scale (VAS), and functional activity measured by neck disability index (NDI) at the end of the therapy. The level of statistical significance was set as p < 0.05. In the two groups, cervical ROM, VAS, and functional scores showed significant changes. Both HILT plus exercise and US/TENS plus exercise effectively increased cervical ROM and reduced pain (with a significant greater decrease in group A). Statistically significant differences in NDI scores were observed after treatment sessions with better results for participants enrolled in group A (HILT plus exercise) Both therapeutic modalities demonstrated analgesic efficacy and improved function in patients affected by cervical spondylosis 4 weeks after the therapy. HILT plus exercise was more effective than US/TENS plus exercise. HILT can be promoted and used in this pathology with positive outcomes. However, further studies are needed to optimize the dose and duration of HILT therapy.